Concussion assessment in the emergency department: a preliminary study for a quality improvement project. Issue 1 (27th December 2018) - Mistry, Dylan A; Rainer, Timothy H
Abstract : Background: In sport, concussion is assessed using the Sports Concussion Assessment Tool (SCAT) 5 and managed with return to play guidelines. Similar, user-friendly tools are rarely, if ever, used in the emergency department (ED). Objectives: To evaluate a modified concussion assessment tool designed for the ED (ED-CAT) in patients presenting with a head injury and to identify variables that predict 30-day reattendance. Methods: A preliminary, prospective, evaluation in a quality improvement project was conducted in one hospital in South Wales. Patients were recruited if they were over 13 years, and either did not have an ED-CT head scan or had a scan with no acute changes. The primary outcome was 30-day reattendance. Results: 40 patients were recruited, 18 of whom had a CT scan. 37 were discharged on the same day with advice, two discharged the next day and one was admitted. Three (7.5%) patients reattended the department. Predictors of reattendance were headache score (median 3.0 vs 5.0; p<0.05), pressure in head score (2.0 vs 5.0; p<0.05), nausea/vomiting score (1.0 vs 3.0; p<0.05), dizziness score (1.0 vs 4.0; p<0.05), blurred vision score (0 vs 4.0; p<0.01), balance problems score (0 vs 4.0; p<0.05), sensitivity to light and confusion score (0 vs 4.0; p<0.01), orientation score (1. 0 vs 0; p<0.05) and immediate memory score (5.0 vs 4.0; p<0.05). Conclusions: Key symptoms and signs predicted 30-day reattendance. The ED-CAT requires validation and refinement in a larger population to produce a short, practical, user-friendly, relevant tool for ED head injury assessment.